Polarizabilities, Susceptibilities and Electron Ionization Cross-sections of Some Organic Monoazides - Arora, U.S.; Chopra, J.R. (Asian Journal of Chemistry, 2010)
A semi-empirical delta-function potential model of chemicalbinding has been employed to compute mean molecularpolarizabilities, diamagnetic susceptibilities and electron ionizationcross-sections of some organic monoazides. The results are brieflydiscussed.